Challenging Structure Elucidation of Lumnitzeralactone, an Ellagic Acid Derivative from the Mangrove Lumnitzera racemosa - Jonas Kappen; Jeprianto Manurung; Tristan Fuchs; Sahithya Phani Babu Vemulapalli; Lea M. Schmitz; Andrej Frolov; Andria Agusta; Alexandra N. Muellner-Riehl; Christian Griesinger; Katrin Franke; Ludger A. Wessjohann (Marine Drugs, 2023)
The previously undescribed natural product lumnitzeralactone (1), which represents a derivative of ellagic acid, was isolated from the anti-bacterial extract of the Indonesian mangrove species Lumnitzera racemosa Willd. The structure of lumnitzeralactone (1), a proton-deficient and highly challenging condensed aromatic ring system, was unambiguously elucidated by extensive spectroscopic analyses involving high-resolution mass spectrometry (HRMS), 1D 1H and 13C nuclear magnetic resonance spectroscopy (NMR), and 2D NMR (including 1,1-ADEQUATE and 1,n-ADEQUATE). Determination of the structure was supported by computer-assisted structure elucidation (CASE system applying ACD-SE), density functional theory (DFT) calculations, and a two-step chemical synthesis. Possible biosynthetic pathways involving mangrove-associated fungi have been suggested.